Association between measures of vitamin A and the ocular fundus findings in cerebral malaria. - Lewallen, S; Taylor, T; Molyneux, M; Semba, R; Wills, B; Courtright, P (1998)
OBJECTIVE: To investigate the relationship between serum vitamin A levels and conjunctival impression cytology and retinal whitening present in Malawian children with cerebral malaria. METHODS: Standard retinal examination and conjunctival impression cytology were performed at hospital admission on 101 consecutively admitted children with cerebral malaria. Blood samples were drawn from 56 children at 24 hours, frozen at -20 degrees C, and transported for assessment of vitamin A levels by high-performance liquid chromatography. Associations among fundus findings and vitamin A measurements were sought. RESULTS: The whitening of the retina that we have previously described in children with cerebral malaria was found to be associated with a mean+/-SD serum vitamin A level of 0.29+/-0.1 micromol/L, compared with a mean vitamin A level of 0.41+/-0.2 micromol/L in children without retinal whitening. Children with retinal whitening were 2.77 (95% CI, 1.06-7.3) times more likely to have abnormal conjunctival impression cytology results than those without whitening. No child had any clinical or ophthalmologic evidence of chronic vitamin A deficiency. CONCLUSIONS: The retinal whitening described in children with cerebral malaria is associated with low serum vitamin A levels and with abnormal conjunctival impression cytology results and may be due to acute vitamin A deficiency at the tissue level.